Lenslet array-free efficient coherent combining of broadband pulses at the output of a multicore fiber with a square core grid - Kalinin, Nikolay A.; Anashkina, Elena A.; Leuchs, Gerd; Andrianov, Alexey (Optics Express, 2022)
An efficient optical scheme for coherent combining of radiation from the output of a multicore fiber (MCF) with a square array of cores in the out-of-phase supermode is proposed. The scheme uses only simple optical elements and is suitable for an arbitrary number of MCF cores. In a proof-of-concept experiment broadband pulses transmitted through a 25-core fiber were combined with 81% efficiency and good beam quality. In numerical modeling a close to unity efficiency is obtained for a large number of cores. The proposed scheme can be used in a reverse direction for efficient beam splitting and launching the out-of-phase supermode into the MCF.
CRIS-Team Scopus Importer:2023-04-20